Impact of transfer pricing toward benefits and sustainable of multinational hotel industry - Widjaja, Gunawan (Linguistics and Culture Review, 2021)
This article discusses the impact of transfer pricing on the benefits and sustainability of the hotel industry operating in many countries. The author believes that the hotel industry is just like any other industry where the impact of transfer pricing also impacts tax reporting and the company's actual financial condition. For this reason, we have made some databases of journal publications and websites as the primary data for us to study with a phenomenological approach so that these data become valid findings in completing the discussion of this business study. The descriptive qualitative study format became the design of this study by relying on data and evidence from field studies by digitally searching in journal publications such as Taylor and Francis, Elsevier, Google books, and many national scientific publications. Based on the study results and discussion of the data, we can summarize that transfer pricing impacts revenue on the sustainability of the hotel industry internationally. Therefore, transfer pricing rules, and policies for each hotel are allowed to be directly determined following the country's rules in which it is located the hotel operated.